Contribution of disulfide bond to the stability of Thermobifida fusca cutinase. (February 2019) - Chen, Sheng; Wu, Yufei; Su, Lingqia; Wu, Jing
Abstract: Cutinase is versatile enzyme which can be widely applied in the food industries. Thermobifida fusca cutinase Tfu_0882 possess one disulfide bond and exhibit superior thermostability. By heat capacity calculation, this disulfide bond is the determinant for thermostability of T. fusca cutinase. To further investigate its contribution, cutinase mutant lacking the disulfide bond (C241A/C259A) was constructed and expressed in Escherichia coli . The extracellular production of C241A/C259A cutinase decreased dramatically to 13.8%, and large amounts of insoluble inclusion bodies were detected in cell. The catalytic efficiency of purified C241A/C259A cutinase decreased to 71.0%. In addition, the thermostability of C241A/C259A cutinase reduced significantly and the secondary structure changed distinctly by CD spectra analysis.